2008
DOI: 10.1016/j.molimm.2006.11.026
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis of the host defense peptide Human Beta Defensin-1: New insight into its potential role in cancer

Abstract: Although it is known that innate immunity is key for protecting the body against foreign agents such as bacteria, little is known about elements of the innate immune system that have anti-tumor activity. Human Beta Defensin-1 (hBD-1), an important component of the innate immune response, is lost at high frequencies in malignant prostatic tissue, while high levels of expression are maintained in adjacent benign regions. In prostate carcinoma, frequent genetic alterations occur in the 8p22-23 region and several … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
78
1
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(98 citation statements)
references
References 24 publications
8
78
1
2
Order By: Relevance
“…However, further significant differences in alterations were seen including more frequent losses of chromosome 17p13 carrying the TP53 gene in EGFR-wt tumors and losses in chromosome 8p23 in EGFRmut tumors. Earlier data suggested that the high allelic loss frequencies seen at 8p23 loci could be the result of activation of one or more specific suppressor genes [34] possibly such as host defence peptide Human Beta Defensin-1 [35].…”
Section: Discussionmentioning
confidence: 99%
“…However, further significant differences in alterations were seen including more frequent losses of chromosome 17p13 carrying the TP53 gene in EGFR-wt tumors and losses in chromosome 8p23 in EGFRmut tumors. Earlier data suggested that the high allelic loss frequencies seen at 8p23 loci could be the result of activation of one or more specific suppressor genes [34] possibly such as host defence peptide Human Beta Defensin-1 [35].…”
Section: Discussionmentioning
confidence: 99%
“…Dying tumor cells following chemotherapy and radiotherapy release HMGB1, which can induce the maturation of DCs via TLR2 and TLR4 to promote a cytotoxic T lymphocyte response through cross-presentation of tumor antigens (94)(95)(96). Various defensins have been found to have tumor suppressor properties (97)(98)(99) and are significantly downregulated in various carcinomas, including DEFB1 in renal cell and prostate carcinomas and DEFB4A and α-defensin HNP-2 in cervical squamous cell carcinomas. Furthermore, although data on the role of α-defensins in cancer biology are currently lacking, they may be antiangiogenic, acting by disrupting fibronectin signaling via the α5β1 integrin (100).…”
Section: Cancermentioning
confidence: 99%
“…This study showed that growth of an OSCC cancer cell line decreased after the addition of hBD1, but increased after treatment with hBD2 or hBD3. Similarly, in prostate cancer cells, hBD1 was shown to decrease the growth rate [104]. Expression of hBD1 in late-stage prostate cancer cell lines (PC3 and DU145) caused rapid cell death.…”
Section: The Role Of β-Defensins In Cancermentioning
confidence: 99%